The Portrayal of Islam in Some Early Nigerian Newspapers (1880-1910) (American Journal of Islam and Society, 1989)
The history of Islam in part of what is known today as Nigeria datesto about the loth Century. Christianity dates to the late 18th Century. Bythe middle of the 19th Century, when Nigerian newspapers began to appearon the streets of Nigeria, both religions had won so many followers and extendedto so many places in Nigeria that very few areas were untouched bytheir influence. The impact of both religions on their adherents not only determinedtheir spiritual life, but influenced their social and political lives aswell. It therefore became inevitable that both religions receive coverage frommost of the newspapers of the time. How the newspapers as media of informationand communication reported issues about the two religions is thetheme of this paper.Rationale for the StudyThe purpose of this study is to highlight the context in which such earlynewspapers operated and the factors that dictated their performance. Thisis because it is assumed that when a society faces external threat to its territory,culture, and independence, all hands (the press inclusive) ought tobe on deck to resist the threat with all might. Were newspapers used as verbalartillery and how did they present each religion? It is also assumed thatin a multireligious society a true press should be objective and serve as avanguard in the promotion of the interest of the people in general and notcreate or foster an atmosphere of religious conflict. The study also aims atfinding out whether the papers promoted intellectual honesty and fosteredthe spirit of unity particularly when the society was faced with the encroachmentof the British who posed a threat to their freedom, culture, economy ...